AFAP1 antisense RNA 1 promotes retinoblastoma progression by sponging microRNA miR-545-3p that targets G protein subunit beta 1. Issue 3 (1st March 2022) - Tang, Wenting; Zhang, Li; Li, Jing; Guan, Yu
ABSTRACT: The oncogenic role of actin filament-associated protein 1 antisense RNA 1 (AFAP1-AS1) has been reported in retinoblastoma (RB). However, the underlying regulatory mechanisms remain poorly understood. In this study, reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and Western blotting were performed to analyze the expression of AFAP1-AS1, microRNA miR-545-3p, or G protein subunit beta 1 (GNB1). Cell Counting Kit-8 (CCK-8) and Transwell migration assays were used to detect cell proliferation and migration. In addition, caspase-3 activity was monitored by caspase-3 activity assay. Luciferase reporter assays combined with RNA immunoprecipitation (RIP) and pull-down assays were performed to elucidate the target relationship between miR-545-3p and AFAP1-AS1 or GNB1. Xenograft tumor experiments were performed to evaluate RB cell growth in vivo . Increased AFAP1-AS1 and GNB1 expression in RB tissues and cells was confirmed by RT-qPCR; conversely, miR-545-3p was found to be downregulated in RB tissues and cells. AFAP1-AS1 overexpression resulted in increased proliferation and migration of RB cells, whereas AFAP1-AS1 silencing resulted in decreased proliferation and migration of RB cells. Moreover, AFAP1-AS1 was found to target miR-545-3p. The anti-miR-545-3p treatment phenocopied the effect of AFAP1-AS1 overexpression and promoted RB cell growth in vivo . miR-545-3p was found to directly target GNB1. GNB1 silencing resulted in reduced proliferation and migration of RB cells and attenuated the oncogenic effect of the miR-545-3p inhibitor. Thus, in this study, a novel ceRNA regulation network of AFAP1-AS1 in RB was identified, where AFAP1-AS1 regulated GNB1 expression by targeting miR-545-3p, ultimately driving RB progression.